2008
DOI: 10.1371/journal.pone.0003326
|View full text |Cite
|
Sign up to set email alerts
|

Polymicrobial Nature of Chronic Diabetic Foot Ulcer Biofilm Infections Determined Using Bacterial Tag Encoded FLX Amplicon Pyrosequencing (bTEFAP)

Abstract: BackgroundDiabetic extremity ulcers are associated with chronic infections. Such ulcer infections are too often followed by amputation because there is little or no understanding of the ecology of such infections or how to control or eliminate this type of chronic infection. A primary impediment to the healing of chronic wounds is biofilm phenotype infections. Diabetic foot ulcers are the most common, disabling, and costly complications of diabetes. Here we seek to derive a better understanding of the polymicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
433
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 497 publications
(456 citation statements)
references
References 49 publications
20
433
0
3
Order By: Relevance
“…The specificity of the amplification products was further confirmed by melting curve analyses, and the expected sizes of the amplified fragments were checked on a 1 % agarose gel. Overall, average efficiencies for February (RS) September (DS) 1 6 S Ta g -E n c o d e d F L X -T i t a n i u m A m p l i c o n Pyrosequencing Bacterial and archaeal tag-encoded FLX amplicon pyrosequencing (bTEFAP and aTEFAP, respectively), analyses by means of a Roche 454 FLX instrument with titanium reagents, were performed at the Research and Testing Laboratory (Lubbock, TX, USA) as described previously [37,38]. The PCR primers for FLX amplicon pyrosequencing were chosen to span the variable V1-V3 regions in the 16S rRNA gene: 27 F (5′-GAGTTTGATCNTGGCTCAG-3′) and 519R (5′-GWNTTACNGCGGCKGCTG-3′) for bacteria and V3-V4 regions ARCH 349 F (5′-GYGCASCAGKCGMGAAW-3′) and ARCH 806R (5′-GGACTACVSGGGTATCTAAT-3′) for archaea.…”
Section: Methodsmentioning
confidence: 99%
“…The specificity of the amplification products was further confirmed by melting curve analyses, and the expected sizes of the amplified fragments were checked on a 1 % agarose gel. Overall, average efficiencies for February (RS) September (DS) 1 6 S Ta g -E n c o d e d F L X -T i t a n i u m A m p l i c o n Pyrosequencing Bacterial and archaeal tag-encoded FLX amplicon pyrosequencing (bTEFAP and aTEFAP, respectively), analyses by means of a Roche 454 FLX instrument with titanium reagents, were performed at the Research and Testing Laboratory (Lubbock, TX, USA) as described previously [37,38]. The PCR primers for FLX amplicon pyrosequencing were chosen to span the variable V1-V3 regions in the 16S rRNA gene: 27 F (5′-GAGTTTGATCNTGGCTCAG-3′) and 519R (5′-GWNTTACNGCGGCKGCTG-3′) for bacteria and V3-V4 regions ARCH 349 F (5′-GYGCASCAGKCGMGAAW-3′) and ARCH 806R (5′-GGACTACVSGGGTATCTAAT-3′) for archaea.…”
Section: Methodsmentioning
confidence: 99%
“…Initial generation of the sequencing library involved a one-step PCR of 30 cycles, using a mixture of Hot Start and HotStar high-fidelity taq polymerase, as described previously (Dowd et al, 2008). Tag-encoded FLX amplicon pyrosequencing analyses utilised Roche 454 FLX instrument (Roche, Branford, CT, USA) with Titanium reagents, titanium procedures performed at the Research and Testing Laboratory (Lubbock, TX, USA) using RTL protocols (www.researchand testing.com).…”
Section: Pyrosequencingmentioning
confidence: 99%
“…Sequences with ambiguous base calls and sequences with homopolymers 46 bp were removed. Further, any non-bacterial ribosome sequences and chimeras were removed using Black Box Chimera Check software (B2C2) (Gontcharova et al, 2010), as has been described previously (Dowd et al, 2008). To determine the identity of bacteria in the remaining sequences, sequences were de-noised, assembled into OTU clusters at 97% identity and queried using a distributed NET algorithm that utilises Blastn Ăž (Kraken BLAST; www.krakenblast.com) against a database of high-quality 16S bacterial sequences.…”
Section: Sequence Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…This is significantly different from the results of the majority of studies, in which DFUs are polymicrobial in nature. [13][14][15][16][17][18][19][20][21][22] However, some studies have shown lower than expected rates of polymicrobial infection. [1,20,23] Monomicrobial nature of infection is associated with the duration of the ulcer.…”
Section: Discussionmentioning
confidence: 99%